Efeito do óleo essencial de lippia alba nos parâmetros oxidativos do jundiá (Rhamdia quelen) exposto a diferentes concentrações de oxigênio - Azambuja, Cati Reckelberg (2009)
Juvenile silver fish (Rhamdia quelen) were exposed to the essential oil of Lippia alba (L. alba) and transported in plastic bags for different periods (5, 6 and 7 h) yielding final different oxygen levels. The biomarkers of oxidative stress, lipoperoxidation (LPO), catalase (CAT), superoxide dismutase (SOD), and glutathione-S-transferase (GST) were measured in the liver, gills and brain of the fish. The juveniles were assigned to 6 different treatment groups according to the presence or not of the essential oil of L. alba in water (10 μL/L) and the length of transportation, which determined the final concentration of dissolved oxygen inside the bags: Five hours: hyperoxia (13.25 ± 0.35 mg/L O2); hyperoxia with L. alba (11.27 ± 0.22 mg/L O2); Six hours: normoxia (7.35 ± 0.35 mg/L O2); normoxia with L. alba (7.29 ± 0.40 mg/L O2); Seven hours: hypoxia (2.29 ± 0.36 mg/L O2); hypoxia with L. alba (3.82 ± 0.7 mg/L O2). The addition of essential oil of L. alba causes an increase of LPO in the tissues exposed to hyperoxia and a reduction of GST in the fish kept under hyperoxia and hypoxia as compared to those under normoxia. In the tissues there is a reduction of LPO and GST and an increase of SOD in the specimens under hypoxia and a reduction of GST in those under hyperoxia with the oil. These results suggest that the presence of the essential oil of L. alba improves the redox state in the evaluated tissues, both under hyperoxia and under hypoxia.